1957
DOI: 10.2134/agronj1957.00021962004900050013x
|View full text |Cite
|
Sign up to set email alerts
|

Varietal Responses of Soybeans to a Bacterial‐Induced Chlorosis1

Abstract: Sypnosis The degree of susceptibility of 40 varieties of the soybean (Glycine max L.) to a bacterial‐induced chlorosis is reported. Ten varieties showed no chlorosis when given selected inoculants in greenhouse tests; 7 others proved to be negligibly susceptible; 11 varieties showed a light or variable susceptibility; 6 were moderately susceptible; and 6 were highly susceptible. The results are discussed in relation to nodulation and symbiotic nitrogen fixation and yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 1 publication
(1 reference statement)
1
20
0
Order By: Relevance
“…Rhizobitoxine interferes with chlorophyll synthesis in developing leaves producing a distinctive interveinal foliar chlorosis. This foliar chlorosis has been reported in producers' fields in the states of Alabama, Arkansas, California, Florida, Georgia, Mississippi, North and South Carolina, and Tennessee (Erdman et al, 1957).…”
Section: Genetically Defined Traits"mentioning
confidence: 58%
“…Rhizobitoxine interferes with chlorophyll synthesis in developing leaves producing a distinctive interveinal foliar chlorosis. This foliar chlorosis has been reported in producers' fields in the states of Alabama, Arkansas, California, Florida, Georgia, Mississippi, North and South Carolina, and Tennessee (Erdman et al, 1957).…”
Section: Genetically Defined Traits"mentioning
confidence: 58%
“…USDA 110 and 123 are Group I/Ia strains whereas the remainder belong to Group II (Devine et al, 1988;Hollis et al, 1981). Strain USDA 31 may induce light RT symptoms (Erdman et al, 1957), whereas USDA 46 is not documented to be a chlorosis-inducing strain. Strain USDA 31 may induce light RT symptoms (Erdman et al, 1957), whereas USDA 46 is not documented to be a chlorosis-inducing strain.…”
Section: Inoculum Preparation and Greenhouse Culturementioning
confidence: 99%
“…A study by Erdman et al (1957) found that the expression of severe RT symptoms among several soybean cultivars nodulated by B. japonicum strain USDA 76 resulted in decreased vegetative yield and pod weight. A study by Erdman et al (1957) found that the expression of severe RT symptoms among several soybean cultivars nodulated by B. japonicum strain USDA 76 resulted in decreased vegetative yield and pod weight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations